2016
DOI: 10.1074/jbc.m116.720631
|View full text |Cite
|
Sign up to set email alerts
|

Propionate Increases Hepatic Pyruvate Cycling and Anaplerosis and Alters Mitochondrial Metabolism

Abstract: In mammals, pyruvate kinase (PK) plays a key role in regulating the balance between glycolysis and gluconeogenesis; however, in vivo regulation of PK flux by gluconeogenic hormones and substrates is poorly understood. To this end, we developed a novel NMR-liquid chromatography/tandem-mass spectrometry (LC-MS/MS) method to directly assess pyruvate cycling relative to mitochondrial pyruvate metabolism (VPyr-Cyc/VMito) in vivo using [3-13C]lactate as a tracer. Using this approach, VPyr-Cyc/VMito was only 6% in ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 29 publications
2
70
0
Order By: Relevance
“…Such high rates of hepatic pyruvate cycling would use a significant fraction of the ATP available, and place the hepatocyte in a metabolically precarious position. In a recent study we found that an intra-arterial infusion of propionate, that was lower than (Hasenour et al, 2015; Jin et al, 2005; Jin et al, 2004; Satapati et al, 2015) or similar to (Sunny et al, 2011) the total amount of sodium propionate administered in previous studies, dose-dependently increased: hepatic propionyl CoA concentrations up to 18 fold, hepatic pyruvate cycling up to 20–30 fold, hepatic TCA intermediates (malate and succinate) and aspartate by 2–3 fold, and rates of hepatic glucose production by up to 2 fold in awake rats (Perry et al, 2016). It is well established that propionyl CoA potently stimulates pyruvate carboxylase activity and flux (Perry et al, 2016; Scrutton, 1974) and this may explain at least in part the large increases in hepatic pyruvate carboxylase flux and pyruvate cycling that Sunny et al observed in their [1,2,3- 13 C 3 ]propionate labeling studies of hepatic mitochondrial metabolism in humans (Sunny et al, 2011).…”
Section: Resultsmentioning
confidence: 52%
See 4 more Smart Citations
“…Such high rates of hepatic pyruvate cycling would use a significant fraction of the ATP available, and place the hepatocyte in a metabolically precarious position. In a recent study we found that an intra-arterial infusion of propionate, that was lower than (Hasenour et al, 2015; Jin et al, 2005; Jin et al, 2004; Satapati et al, 2015) or similar to (Sunny et al, 2011) the total amount of sodium propionate administered in previous studies, dose-dependently increased: hepatic propionyl CoA concentrations up to 18 fold, hepatic pyruvate cycling up to 20–30 fold, hepatic TCA intermediates (malate and succinate) and aspartate by 2–3 fold, and rates of hepatic glucose production by up to 2 fold in awake rats (Perry et al, 2016). It is well established that propionyl CoA potently stimulates pyruvate carboxylase activity and flux (Perry et al, 2016; Scrutton, 1974) and this may explain at least in part the large increases in hepatic pyruvate carboxylase flux and pyruvate cycling that Sunny et al observed in their [1,2,3- 13 C 3 ]propionate labeling studies of hepatic mitochondrial metabolism in humans (Sunny et al, 2011).…”
Section: Resultsmentioning
confidence: 52%
“…We also directly assessed rates of hepatic pyruvate cycling defined by: (V PK +V ME )/(V PC +V PDH ), where V PK is pyruvate kinase flux, V ME is malic enzyme flux, V PC is pyruvate carboxylase flux and V PDH is pyruvate dehydrogenase flux, by monitoring the relative 13 C labeling in hepatic [2- 13 C]alanine relative to hepatic [2- 13 C]glutamate during an intravenous infusion of [3- 13 C]lactate (Befroy et al, 2015; Perry et al, 2016). Following the start of the [3- 13 C]lactate infusion plasma 13 C lactate enrichments (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations